Murder on the house eaudiobook - Blackwell, Juliet (Haunted Home Renovation, 2013)
Word has spread that contractor Mel Turner can communicate with the spirits of the dead, and she's having a hard time maintaining a low profile. She decides to embrace her reputation for the chance to restore a historic house that calls to her. The new owners, who hope to run a haunted bed-and-breakfast, want Mel to encourage the ghosts that supposedly roam the halls to enhance the house's paranormal charm. The catch: Mel has to spend one night in the house to win the project. During the spine-chilling sleepover, the estate gains another supernatural occupant when someone doesn't survive the night. As Mel tries to coax the resident spirits into revealing the identity of the killer, she risks becoming the next casualty of this dangerous renovation.